Localisation and identification of 3D objects using computer vision - Chua, Chin Seng. (2008)
The objectives of the project is to investigate research methodologies involving range maps: three dimensional range images, particularly in the area of automatically recognizing common, free-forming objects which are represented by their 3D shape, rather than their 2D intensity images.